Analisis Kebutuhan E-LKM Interaktif pada Mata Kuliah Umum Bahasa Indonesia di Universitas Negeri Padang - Nurrahmah, Faiza; Nursaid (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to describe the results of the analysis of the design needs of interactive e-LKM in general Indonesian Language courses. This study was motivated by the low writing skills of students because they were assisted by AI. The subjects of the study were lecturers and 200 students. The method used in this study was a mixed method. The research data were in the form of quantitative and qualitative data consisting of a questionnaire and interview sheets. The results of this study indicate good scientific article writing skills, a student will find it easier to work on final assignments or write other research results. From the concept analysis, it was found that the concept of existing teaching materials is in accordance with the needs of the curriculum, but is not specific so it is necessary to develop specific e-LKM to improve students' writing skills.